Near-infrared chemiluminescent reporters for in vivo imaging of reactive oxygen and nitrogen species in kidneys - Huang, Jingsheng (2021)
Despite the superior sensitivity of chemiluminescence over fluorescence, most chemiluminescence reporters only emit visible light, and have low water solubility, making them poorly equipped for in vivo imaging applications. Herein two near-infrared (NIR) chemiluminescent reporters (NCRs) with high renal clearance for real-time imaging of reactive oxygen and nitrogen species in the kidneys are synthesized. NCRs comprise a β-cyclodextrin unit and a modified dicyanomethylene-4H-pyran containing Schaap's dioxetane as the renal-clearance enabler and the chemiluminescent moiety, respectively. NCR1 and NCR2 specifically activate their NIR chemiluminescence towards superoxide anion (O2•−) and peroxynitrite (ONOO−), respectively. By virtue of their nanomolar sensitivity and high renal clearance, NCRs not only detect subtle upregulation of endogenous RONS in cells but also enable noninvasive monitoring of RONS in the kidneys under nephrotoxic exposure. The earlier activation of NCR1 relative to NCR2 implies the sequential upregulation of O2•− and ONOO− during drug-induced acute kidney injury (AKI). Moreover, detection of the fluorescence of excreted NCRs permits urinalysis of AKI, detecting the upregulation of RONS at least 24 h earlier than histological analysis. Thus, this study not only introduces ultrasensitive NIR chemiluminescent probes but also provides guidelines to transform them into legitimate imaging agents for organ-specific in vivo detection.